Managing information security - Vacca, John R (Waltham, MA Syngress, 2014)
"Managing Information Security offers focused coverage of how to protect mission critical systems, and how to deploy security management systems, IT security, ID management, intrusion detection and prevention systems, computer forensics, network forensics, firewalls, penetration testing, vulnerability assessment, and more. It offers in-depth coverage of the current technology and practice as it relates to information security management solutions. Individual chapters are authored by leading experts in the field and address the immediate and long-term challenges in the authors' respective areas of expertise. Chapters contributed by leaders in the field covering foundational and practical aspects of information security management, allowing the reader to develop a new level of technical expertise found nowhere else. Comprehensive coverage by leading experts allows the reader to put current technologies to work. Presents methods of analysis and problem solving techniques, enhancing the reader's grasp of the material and ability to implement practical solutions". -- Cover
Previous edition: 2010
Includes bibliographical references and index
1
NEW, GENR_KNOWL
Keywords: Computer networks -- Security measures; Computer security -- Management; Electronic data processing departments -- Security measures; Penetration testing (Computer security)